MULTISECTORAL MODELS FOR ADVANCED KNOWLEDGE IN CULTURE AND SPORTS ORGANIZATIONAL ENTITIES, IN SMALL AND MEDIUM COMPANIES - Mihai-Daian, CEAUSU (Strategii Manageriale, 2015)
The article used to identify functional and operational links, and determining the quasi-unlimited ecoknowledge in organizational culture and sports entities, in small and medium firms. It is shown that, in fact, increased in absolute economic indicators of ontemporary productive firms, in organizational culture and sports entities explained increasingly by innovation, springing from some new features, on specific contemporary environment organized / structured in corporate regime, by functional and operational knowledge based economy. Conclusion, for Romania, in the context above, is that the country needs explicit modeling technology diffusion in the structure of the economic climate, by modelers increasingly integrated, including organizational culture and sports entities in small and medium firms.